The study of DNA dynamics at carbon electrode surface toward DNA sensors by fluorescence and electrochemical impedance spectroscopy - Li, Qin (Kansas State University, 2011)
This study is focused on exploring the mechanisms of DNA dynamics at carbon electrode surfaces under a strong electric field for the development of novel DNA hybridization sensors. Oligonucleotides with FAM6 attached at the distal end are covalently tethered on the carbon electrode surface. The fluorescence emission from the FAM6 is strongly quenched in close proximity to the electrode surface. The modulation to the fluorescence intensity is correlated with the reversible reorientation of the negatively charged DNA molecules under the electric field within the electric double layer. The orientation dynamics are apparently determined by the interplay of the electropotential, salt concentration, and stiffness of the DNA molecules. We have observed that dsDNAs switch with fast dynamics (in < 0.05 second) followed by relaxation at a slower rate (in > 0.1 second) when the electric field is altered by stepping the electropotential to a more positive or negative value. The DNA reorientation exhibits strong dependence on the PBS buffer concentration and electric double layer thickness. A preliminary calculation based on dipole-surface energy transfer theory indicates that the critical distance between FAM6 and glassy carbon surface is 10.95 nm. In connection with the fluorescence study, the effect of DNA hybridization on electrochemical impedance spectroscopy (EIS) has also been investigated by two methods in an attempt to develop a fast electronic detection method. First, EIS at high AC amplitude (141 mV rms) with DNA-modified glassy carbon electrodes before and after target DNA hybridization have shown notable change at high frequencies, likely related to the DNA reorientation processes. Second, reversible EIS detection of DNA hybridization has been demonstrated with patterned regular carbon nanofiber arrays at normal AC amplitude (10 mV rms). The combination of these two methods will be explored in future studies. The effects of the electric field on surface-tethered molecular beacons (MBs) have also been studied with fluorescence spectroscopy. An increase in fluorescence at negative bias is observed accompanying the opening of the MB stem, which leads to larger separation between fluorophore and quencher. At positive bias, the rehybridization of the MB stem leads to a decrease in fluorescence intensity.
Keywords: DNA sensors; Electrochemical impedance spectroscopy; DNA dynamics; Electrical double layer; Chemistry (0485)